Improving Interdisciplinary Relationships in Primary Care with the Implementation of TeamSTEPPS - Nicole Siddons (Interdisciplinary Journal of Partnership Studies, 2016)
A major challenge in healthcare is lack of interdisciplinary collaboration (O’Daniel & Rosenstein, 2008). The Institute of Medicine report, To Err is Human: Building a Safer Health System (1999), shows that errors often occur due to lapses in partnership and communication. This article describes the implementation of TeamSTEPPS, an evidence-based tool for optimizing staff relationships and partnership, in a clinic in which a change in the care model had affected interprofessional collaboration and teamwork, threatening healthcare outcomes and staff engagement. The implementation of TeamSTEPPS, customized using elements of IDEO’s (2015) Human-Centered Design, shifted the culture of the clinic towards partnership, resulting in improved staff perceptions of teamwork and statistically significant improvements in the quality of patient care.